Quantification of argyrophillic, argentaffin and insulin immunoreactive cells in the small intestine in the opossum Didelphis aurita (Wied-Neuwied, 1826) - doi: 10.4025/actascibiolsci.v33i4.8644 (Acta Scientiarum. Biological Sciences, 2011)
The objective of this study was to quantify argyrophillic, argentaffin and insulin immunoreactive endocrine cells in the different segments of the small intestine of Didelphis aurita and measure probable differences in the number of these cells between adult and post-pubertal animals. Biological material consisted of ten male and female opossums specimen, divided in two groups according to weigh. The utilized staining techniques were Grimelius, modified Masson-Fontana and direct immunoperoxidase. Results indicated a predominance of argyrophillic cells in the small intestine of opossums from class 1 and 2, with an average of 52.58 and 56.15 cells mm-2, respectively; of which, the average number of total endocrine cells, argyrophillic and argentaffin cells decreased distally in the intestinal segments of opossums from classes 1 and 2. No significant difference was observed for the insulin immunoreactive cells between the intestinal segments of animals from class 2. A greater number of insulin immunoreactive cells was encountered in the jejunum and ileum of animals from class 2 when compared to the same segment in animals from class 1.